FOOD IMPORTATION AND AGRICULTURAL DEVELOPMENT IN NIGERIA: WHITHER RURAL DEVELOPMENT? (2013)
No country can ever develop without integrated rural structures. Unfortunately, rural areas in Nigeria today are usually ghost areas as nearly all the youths have out-migrated, elderly neglected and agriculture has been traded off.The rural areas that used to accommodate over 70 percent of Nigerians has failed in this regard and agriculture that used to employ over 70 percent of Nigerians and used to provide over 70 percent of the foreign exchange earnings of Nigeria has collapsed. Nigeria that used to feed other nations can now not feed itself as it is now one of the biggest importers of food, most of which it can produce and even export. Nigeria spent at least N64 billion on food import in 2010. As at third quarter of 2011, the country has spent N635 billion on the importation of wheat; N356 billion on rice; N217 billion on sugar and N97 billion on fish imports. On the average, Nigeria spends about N1.8 billion on wheat and N1 billion on rice importations daily. Regardless of these huge amounts, at least 53 million Nigerians (about 30 percent) still go hungry while about 90 percent live in poverty of under $2 a day, most being rural dwellers. A dangerous flip side of the rural and agricultural downward trajectories is policy gaps. Thus, this paper explores the contours of food importation, agricultural positions, related policy challenges and implications for sustainable rural development in Nigeria. Strong analytical frameworks were deployed; recommendations made just as reliable conclusions were reached. No country can ever develop without integrated rural structures. Unfortunately, rural areas in Nigeria today are usually ghost areas as nearly all the youths have out-migrated, elderly neglected and agriculture has been traded off. The rural areas that used to accommodate over 70 percent of Nigerians has failed in this regard and agriculture that used to employ over 70 percent of Nigerians and used to provide over 70 percent of the foreign exchange earnings of Nigeria has collapsed. Nigeria that used to feed other nations can now not feed itself as it is now one of the biggest importers of food, most of which it can produce and even export. Nigeria spent at least N64 billion on food import in 2010. As at third quarter of 2011, the country has spent N635 billion on the importation of wheat; N356 billion on rice; N217 billion on sugar and N97 billion on fish imports. On the average, Nigeria spends about N1.8 billion on wheat and N1 billion on rice importations daily. Regardless of these huge amounts, at least 53 million Nigerians (about 30 percent) still go hungry while about 90 percent live in poverty of under $2 a day, most being rural dwellers. A dangerous flip side of the rural and agricultural downward trajectories is policy gaps. Thus, this paper explores the contours of food importation, agricultural positions, related policy challenges and implications for sustainable rural development in Nigeria. Strong analytical frameworks were deployed; recommendations made just as reliable conclusions were reached.